Romanticism - and Byron. - Cochran, Peter (Cambridge Scholars Pub., 2009)
""Romanticism - and Byron"" is a book in two parts. In the first part, Dr Cochran examines ""Romanticism"" and shows that it is a word meaning anything, and therefore nothing. It is an academic construct created by academics, and has no basis in the writings of the early nineteenth century. Its continued use, argues Dr Cochran, is a modern marketing phenomenon solely. In the second part, Dr Cochran examines the life and work of Byron in the non-""romantic"" context of his contemporaries. He sho ...